Minimizing opportunity costs to aquatic connectivity restoration while controlling an invasive species. Issue 4 (29th May 2018) - Milt, Austin W.; Diebel, Matthew W.; Doran, Patrick J.; Ferris, Michael C.; Herbert, Matthew; Khoury, Mary L.; Moody, Allison T.; Neeson, Thomas M.; Ross, Jared; Treska, Ted; O'Hanley, Jesse R.; Walter, Lisa; et al.
Abstract: Controlling invasive species is critical for conservation but can have unintended consequences for native species and divert resources away from other efforts. This dilemma occurs on a grand scale in the North American Great Lakes, where dams and culverts block tributary access to habitat of desirable fish species and are a lynchpin of long‐standing efforts to limit ecological damage inflicted by the invasive, parasitic sea lamprey ( Petromyzon marinus ). Habitat restoration and sea‐lamprey control create conflicting goals for managing aging infrastructure. We used optimization to minimize opportunity costs of habitat gains for 37 desirable migratory fishes that arose from restricting sea lamprey access (0–25% increase) when selecting barriers for removal under a limited budget (US$1–105 million). Imposing limits on sea lamprey habitat reduced gains in tributary access for desirable species by 15–50% relative to an unconstrained scenario. Additional investment to offset the effect of limiting sea‐lamprey access resulted in high opportunity costs for 30 of 37 species (e.g., an additional US$20–80 million for lake sturgeon [ Acipenser fulvescens ]) and often required ≥5% increase in sea‐lamprey access to identify barrier‐removal solutions adhering to the budget and limiting access. Narrowly distributed species exhibited the highest opportunity costs but benefited more at less cost when small increases in sea‐lamprey access were allowed. Our results illustrate the value of optimization in limiting opportunity costs when balancing invasion control against restoration benefits for diverse desirable species. Such trade‐off analyses are essential to the restoration of connectivity within fragmented rivers without unleashing invaders. Abstract : Article impact statement : Limiting aquatic connectivity for invasive species can disproportionately reduce potential connectivity restoration for desirable species.